Tubercular Lymphadenitis Mimicking Findings of Metastatic Signet Cell Carcinoma in FNAC: A Case Report - Mainali, Nirajan; Nepal, Niraj; Choudhary, Prabesh Kumar; Uprety, Agraj (Nepalese Medical Journal, 2019)
Tubercular lymphadenitis is one of the most common extrapulmonary tubercular lesions presented in the Outpatient Department which is commonly diagnosed by Fine needle aspiration cytology. Cytological diagnosis of tuberculosis requires the presence of epithelioid cell granulomas demonstration with or without Langhan’s giant cells and necrosis. Sometimes, there can a proliferation of signet like cells without granulomas, which in a cervical lymph node can be given a false interpretation of metastatic signet cell carcinoma. A 35 year female patient with a complaint of cervical lymphadenopathy came to the medical OPD. FNAC was done which showed numerous scattered signet ring cells. However, epithelioid cell granulomas weren’t observed in the smears. Zeihl Neelsen stain for Acid fast bacilli was done but the organism wasn’t appreciated. A biopsy was done and a histopathological slide showed epithelioid cell granulomas and Langhan’s giant cell. Zeihl Neelsen Stain for Acid fast bacilli, which was positive.